Синтез вузла з’єднання ліній передачі НВЧ з провідниковими елементами зв’язку - Захарія, Й. А. (Видавництво Львівської політехніки, 2015)
Пропонується числовий метод синтезу вузла з’єднання ліній передачі НВЧ з перетворенням виду ТЕМ–хвилі на ТЕ-хвилю у хвилеводі. При цьому результати електродинамічного аналізу елемента зв’язку ліній тут не розглядаються, а вважаються заданими. Методом теорії мереж НВЧ визначаються елементи матриці розсіювання вузла з’єднання, які використано для розрахунку ширини смуги робочих хвиль вузла. Пропонується також розширення смуги робочих хвиль вузла вибором величини хвильового опору лінії. The transition two-port (TT) for VHF transmission lines, as is known, transforms the wave type, frequently the TEM line wave mode into TE waveguide mode, and vice versa. In TT structure the most important is line junction-element (exciter) type (vibrator, coil, a. o.), and also reactance type for TT tuning. Thus it is possible to present the TT structure as the junction-three-port (JT), whose one port is by tuning reactance loaded. As an example in the paper is a TT with vibrator junction-element for coaxial line and rectangular waveguide considered. The tuning reactance here is a section of shorted waveguide. Main characteristic quantity for TT device is the wavelength-band width, and corresponding value of reflection coefficient. Usually for TT device the middle wavelength of band-width is given. At the designing of TT device it is necessary all efforts for wavelengthband widening to made. Such the optimization problem for geometrical sizes of TT structure elements arise. The proposed here TT synthesis algorithm is on results of junction-element (exciter) electrodynamics’ analysis based. These results are in analytical part of synthesis algorithm used. For that calculation the VHF circuit theory is applied. In high regret, the electrodynamics’ analysis results we get from none closed expressions in numerical form. Therefore we are forced the numerical synthesis to realize, for which geometrical sizes of junction-element structure must be given. In our case by electrodynamics’ analysis we get the value of input impedance and argument of transmission coefficient between coaxial line and waveguide JT ports. These numerical values serve for scattering matrix elements of JT calculations, use the equations for loss free structure. By aid of one contour signal flow graph reflection coefficient from TT input, and corresponding wave-band width is determined. The mentioned above numerical synthesis algorithm expects the zero value of reflection coefficient from TT input at the middle wavelength, and correspondingly narrow wavelengthband width. The line wave-resistance value can be for that calculation sufficient low accepted.
Synthesis of transition two-port for VHF transmission lines with conducting junction-elements
Keywords: коаксіальна лінія/хвилевід; coaxial line/waveguide transition